2022
DOI: 10.3389/fpsyg.2022.968902
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vaccination beliefs regarding vaccination benefits and COVID-19 fear on the number of vaccination injections

Abstract: The Coronavirus disease pandemic of 2019 is a vast worldwide public health hazard, impacting people of all ages and socioeconomic statuses. Vaccination is one of the most effective methods of controlling a pandemic like COVID-19. This study aims to investigate the relationship between the number of vaccination injections and fear of COVID-19 and test whether beliefs benefit from vaccination COVID-19 mediate the effect of fear of COVID-19 on the number of vaccination injections. A total of 649 Vietnamese adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 112 publications
1
3
0
Order By: Relevance
“…Generally, participants perceived COVID-19 vaccines as beneficial, consistent with other previous studies [ 24 ]. They had a good perception of COVID-19 vaccines, aligning with previous research [ 6 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…Generally, participants perceived COVID-19 vaccines as beneficial, consistent with other previous studies [ 24 ]. They had a good perception of COVID-19 vaccines, aligning with previous research [ 6 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
“… 30 55 Hoang et al reported a similar level of concern about vaccine efficacy and safety and AEFI between immunised and unimmunised groups. 45 We found that the willingness to get vaccinated was higher among the general population, less to significantly low among parents of children aged 5–11 years and children aged 5 years or under receiving COVID-19 vaccines. The national COVID-19 vaccine coverage in Vietnam was remarkably high among targeted populations: the primary COVID-19 dose for adults and children aged 12 years and older reached almost 100%, the percentage of the children aged 5–11 years who completed their first and second doses of COVID-19 vaccines was roughly 86.4% and 69.3%, respectively, as of February 2023.…”
Section: Discussionmentioning
confidence: 65%
“…60 Parents were more likely to want to vaccinate their children if the mortality rate associated with COVID-19 infection rose, following the introduction of new COVID-19 variants. 61 Addition to AEFI, parents expressed a high level of concern about the rapid development of vaccines (>80%) and perceptions that vaccination was unnecessary, resulting in hesitation or refusal, 45 46 which suggests that Vietnam needs to develop a tailored communication strategy in the new context of the pandemic—low infection and mortality rates and high perceived AEFI—if the country plans to roll out national vaccination against COVID-19 for children aged 5 years and younger.…”
Section: Discussionmentioning
confidence: 99%
“…Although the disease provoked by the new coronavirus is potentially health damaging and even deadly, our findings indicate that the fear generated by these risks fosters the intention to vaccinate only in people who have low adherence to conspiracy theories. The positive influence of fear of COVID-19, associated with the high risk of contracting this disease and to its severity, on vaccination intentions and attitudes has previously found when this factor was analyzed independently (e.g., Bendau et al, 2021 ; Chu and Liu, 2021 ; Lielsvagere-Endele et al, 2022 ; Nguyen et al, 2022 ; Rosli et al, 2022 ). However, our study suggests that conspiracist beliefs on this topic moderate this effect by limiting and even canceling it.…”
Section: Discussionmentioning
confidence: 82%